Do blood cultures need continuous monitoring so that clinical action can be taken outside normal working hours?. Issue 11 (November 1995) - Murdoch, D A; Koerner, R J; Speirs, G E; MacGowan, A P; Reeves, D S
Abstract : Many automated blood culture reading systems monitor bacterial growth 24 hours a day but it is unclear if reacting to prompts indicating bacterial growth outside normal laboratory hours is of clinical benefit. An analysis of 50 blood cultures from 43 patients which had organisms seen on Gram films and had triggered positive out-of-hours showed that examination of the Gram film altered management of seven patients and the results of culture or sensitivity testing altered that of a further four. However, after review, it was felt the clinical outcome would not have been influenced by earlier intervention in any of these patients. We therefore consider that an out-of-hours service for dealing with positive blood cultures is not justified in our hospital. This conclusion may not apply universally, especially in hospitals where potential pathogens show less predictable antimicrobial sensitivity patterns.